Plant-available silicon in paddy soils as a key factor for sustainable rice production in Southeast Asia - Klotzbücher, Thimo; Marxen, Anika; Vetterlein, Doris; Schneiker, Janina; Türke, Manfred; van Sinh, Nguyen; Manh, Nguyen Hung; van Chien, Ho; Marquez, Leonardo; Villareal, Sylvia; Bustamante, Jesus Victor; Jahn, Reinhold (Basic and applied ecology, 2015)
Rice is among the most important crops for human nutrition. The need to increase yields is commonly achieved by agricultural intensification that often comes along with negative impacts on the environment. In 2011, the interdisciplinary LEGATO project was launched with the aim to advance sustainable rice production. A key feature for sustainable rice production is silicon (Si) availability. Si can e.g. improve rice crop resistance against pathogens and prevent the uptake of toxic metals. Herein, we introduce the characteristics of the seven LEGATO study regions in Vietnam and the Philippines (i.e., climate, geology, soils, agricultural practices) ranging from lowlands with intensive production to mountain regions with extensive and traditional production systems. Secondly, we show data on concentrations of plant-available Si (Sipa) in topsoils of paddy fields (Ap+Arp horizons) and of sites with an alternative land-use (forest, upland crops), and discuss factors determining spatial differences in Sipa concentrations. Results show that Sipa concentrations in topsoils of paddies (assessed by acetate extraction) greatly differ between Philippine (141–322mg Sikg−1) and Vietnamese (20–51mg Sikg−1) regions. This can be explained by differences in geo-/pedologic conditions between the countries. Large Sipa concentrations in the Philippines are due to recent rock formation by active volcanism, hence, by a large Sipa input due to mineral weathering in recent geologic history. Land-use can also affect Sipa in topsoils: in Philippine regions, Sipa concentrations were significantly larger for paddies than for other land-use types. In some of the Vietnamese paddies, Sipa concentrations are below critical values, thus might limit plant growth. Many Vietnamese farmers export Si from fields by removing straw residues with the harvest. Our subsequent research thus aims to test whether changes in harvest residue management can improve the Si supply to plants in Vietnamese regions. Reis stellt für einen Großteil der Menschen die Hauptnahrungsgrundlage dar. Der in den letzten Jahrzehnten gestiegene Reisbedarf konnte durch eine Intensivierung des Reisanbaus gedeckt werden, was aber oft zu erheblichen Umweltschäden führte. Das seit 2011 laufende interdisziplinäre LEGATO-Projekt hat eine Verbesserung der Nachhaltigkeit beim Reisanbau zum Ziel. Ein wichtiger Aspekt hierbei ist ein nachhaltiges Management des Silizium (Si)-Kreislaufs. Si erhöht die Resistenz der Reispflanze gegen Krankheitserreger, steigert die Effizienz von NPK-Düngern und kann die Aufnahme von toxischen Metallen verringern. In diesem Artikel stellen wir die Untersuchungsregionen des LEGATO-Projekts vor (Klima, Geologie, Böden, landwirtschaftliche Praxis), zeigen Konzentrationen von pflanzenverfügbarem Si (Sipa) in den Reisböden (Ap+Arp-Horizonte) und diskutieren Faktoren, welche Unterschiede der Konzentrationen zwischen den Regionen steuern. Das Sipa wurde mittels Extraktion mit Natrium-Acetat-Lösung bestimmt. Die Ergebnisse zeigen, dass die Sipa-Konzentrationen in philippinischen Böden deutlich höher liegen als in vietnamesischen Böden (141–322 vs. 20–51mg Sikg−1). Dies ist durch Unterschiede der geo-/pedologischen Bedingungen zu erklären. Die hohen Konzentrationen in philippinischen Böden entstehen durch die Freisetzung großer Mengen an mobilem Si während der Verwitterung vulkanischer Gesteine, die in der geologisch jüngeren Geschichte gebildet wurden. Auch die Landnutzung kann die Sipa-Konzentrationen in Oberböden beeinflussen. Die Konzentrationen in philippinischen Reisböden sind höher als die in Böden unter anderer Landnutzung (z.B. Wald, Gemüseanbau). In einigen vietnamesischen Reisfeldern könnte ein Si-Mangel den Reisertrag limitieren. Viele vietnamesische Bauern exportieren Reisstroh nach der Ernte und entziehen dem Kreislauf dadurch eine möglicherweise wichtige Quelle von Sipa. Wir werden deshalb als Nächstes untersuchen, ob man durch eine Änderung dieser Praxis die Si-Versorgung der Reispflanzen verbessern kann.